Implementation of Roll-on Roll-off Shipping Program Davao, Philippines – Bitung, Indonesia - Mamentu, Michael (Borong Newinera Publisher, 2024)
In April 2017, President Jokowi and Philippine President Rodrigo Duterte agreed to open a trade cruise between General Santos Davao and Bitung, North Sulawesi. The goal is not only to strengthen relations between fellow ASEAN member countries, but also to realize the ASEAN Economic Community agreement in a more concrete form. This deal was later named